A circulação de conhecimentos nas atas do ENPEC sobre a integração das artes do ensino de ciências - Nunes, Maynara Menezes (2022)
The present dissertation aimed to develop the construction of a State of the Art to investigate the production of works published in the Proceedings of the National Meeting of Research in Science Education (ENPEC), which dealt with the integration between Art and Science in Science Teaching, which led to the understanding of the relationships existing in the works on the integration of art in science teaching. Ludwik Fleck's theory of knowledge based the research in the epistemological and methodological scope and allowed the characterization of the types of knowledge circulation present in the ENPEC minutes. The search for articles included all the years that the aforementioned event was held, with the exception of only one of these years, since these same works were withheld and without access to the research. The articles were chosen based on their titles and abstracts, that is, the relationship with some type of known art had to be present; they went through the cleavage phase, that is, through exclusion and inclusion criteria for choosing those who would compose the sample. For the choice and selection of the articles presented, their title was evaluated, as mentioned above, plus its abstract; the objective was to identify whether such works were about the integration of some type of art into science teaching. When reading the abstracts, some works were excluded, even though they mentioned some type of art, since they did not contain the proposal to integrate artistic movements into teaching. However, not all abstracts were able to express the central ideas of the work, many mentioned the use of some type of art, but allowed some margins of doubt, if they could compose the sample, nevertheless they were chosen in the first survey, soon after, the selected works were tabulated and analyzed. In such a way that it was possible to identify the quantity of the works, the types of art most used in the construction of the works, their places of origin and which audience these works were aimed at. After the end of the analyses, it was possible to outline the conjunctures about the circulation of thoughts found in the sampling. Both the inter-collective circulation of ideas and the intracollective circulation of ideas were identified. This identification took place through the analysis of a set of characteristics that allowed defining the occurrence and type of circulation that took place between the articles, such as the way in which the art/science relations are addressed in the articles, the methods and techniques used. by the authors, the areas of knowledge that are researching on this theme and the formation of the authors of the articles, the universities of origin of the authors, which authors were cited in a significant amount of times. Thus, it was possible to detect with the reading of the articles, that although there is strong evidence of circulation of thought among the analyzed works, this area of knowledge is still under construction, many authors come from several other fields of knowledge and research on the subject in question, since human social formation is based on interpersonal relationships that also reflect on scientific work; as well as it was possible to conclude that this field of knowledge is still under construction, which points to the need for more detailed studies on this subject.